Understanding DNA and gene cloning - Drlica, Karl. (New York : J. Wiley, 1997)
This book is divided into four parts: Basic molecular genetics; Manipulating DNA; The new molecular genetics; and Human genetics.
Keywords: Molecular cloning; Genetic engineering; Molecular; Molecular cloning; Recombinant DNA; Genetic engineering; Cloning, Molecular